A portable system of X-ray irradiation and heating for electron spin resonance (ESR) dating - Oppermann, Frank; Tsukamoto, Sumiko (Ancient TL, 2015)
In this study we present details of a portable system which contains an X-ray source and heater, designed to irradiate and heat samples within a quartz glass tube for electron spin resonance (ESR) dating. The spatial distribution of the X-ray beam was measured with a radiation sensitive film and the images were scanned and mapped using the Risoescan software. The reproducibility of irradiations was checked by multiple irradiations to alanine. The results confirmed that X-ray irradiations give reproducible doses to samples. The heating component can heat samples between 100◦C and 600◦C and can be used for preheating after irradiation and for resetting the natural signal for regeneration.